2016
DOI: 10.1007/s11043-016-9290-3
|View full text |Cite
|
Sign up to set email alerts
|

Complex order fractional derivatives in viscoelasticity

Abstract: We introduce complex order fractional derivatives in models that describe viscoelastic materials. This can not be carried out unrestrictedly, and therefore we derive, for the first time, real valued compatibility constraints, as well as physical constraints that lead to acceptable models. As a result, we introduce a new form of complex order fractional derivative. Also, we consider a fractional differential equation with complex derivatives, and study its solvability. Results obtained for stress relaxation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Following the same procedure as in [5] in obtaining (16), we conclude that the maximal and minimal values of f (τ, ϕ) and g(τ, ϕ) with respect to τ are f (τ f , ϕ) = ± cos(αϕ) cosh(βϕ) 1 + tg(αϕ) tgh(βϕ) 2 , Proof. Set s = ρe iϕ , ρ = s 2 0 + p 2 , ϕ ∈ [0, π/2].…”
Section: Necessary Estimates For the Laplace Transformmentioning
confidence: 78%
See 2 more Smart Citations
“…Following the same procedure as in [5] in obtaining (16), we conclude that the maximal and minimal values of f (τ, ϕ) and g(τ, ϕ) with respect to τ are f (τ f , ϕ) = ± cos(αϕ) cosh(βϕ) 1 + tg(αϕ) tgh(βϕ) 2 , Proof. Set s = ρe iϕ , ρ = s 2 0 + p 2 , ϕ ∈ [0, π/2].…”
Section: Necessary Estimates For the Laplace Transformmentioning
confidence: 78%
“…Properties of functions f and g for ϕ = π/2 were investigated in [5]. It was shown that the extremal values of f and g are attained at points τ f and τ g respectively, where…”
Section: Thermodynamical Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can define CF t 0 D α t f (t) by (1.1). Since we prefer to work with real valued functions after fractional differentiation, we follow our approach presented in [9] and define combination of (CFFD) of complex order as:…”
Section: )mentioning
confidence: 99%
“…Atanackovi et al established complex order fractional derivatives in models that describe viscoelastic materials in [31]. The authors investigated existence and uniqueness by using a classical fixed point theorem.…”
Section: Introductionmentioning
confidence: 99%